The DEMO-CO2 project: A vadose zone CO2 and tracer leakage field experiment. (August 2015) - Rillard, Jean; Loisy, Corinne; Le Roux, Olivier; Cerepi, Adrian; Garcia, Bruno; Noirez, Sonia; Rouchon, Virgile; Delaplace, Philippe; Willequet, Olivier; Bertrand, Claude
Highlights: Establishment of an experimental monitoring strategy of gas phases during a leakage. Experimental simulation of a leakage of CO2 in the carbonate vadose zone. Use of noble gases (He and Kr) as precursors to monitor CO2 leakage. Use of N2 –CO2 signal and carbon isotopes to distinguish natural CO2 form injected CO2 . Field measurement showed heterogeneous gas transfer in the subsurface. Abstract: The DEMO-CO2 project is dedicated to develop an analytical method for CO2 leakage detection within the vadose zone and to understand the behavior of CO2 in the near subsurface carbonate environment during an induced CO2 leakage. A gas mixture of 3 m 3 of CO2, He and Kr was released at 3.7 m depth in a borehole located in a carbonate vadose zone. Different detection techniques were used to follow the CO2, and noble gas migration within the vadose zone. A numerical simulation done with COORES™ code was used to predict gas flux at surface. Measurements performed in the field showed heterogeneous gas transfer in the subsurface as a result of contrast of permeability/porosity of the porous media at meter scale. Both advective and diffusive gas transfer could be observed due to the different time frames needed to reach maximum He, Kr and CO2 concentrations, confirming that noble gases can be used as precursor of injected CO2 leakage in case of diffusive transfer prevails. Despite the subsurface heterogeneity, simulations results of CO2 flux at the surface were in relatively good agreement with field measurements. The comparison of CO2 concentration with measurements of ubiquitous gas such as N2, coupled with isotopic 13 C analyses could be used to clearly differentiate injected CO2 from natural background CO2 produced by biological activity. Lessons learned through this experiment could help to improve future near-surface gas geochemistry surveys for site assessment, identify CO2 leakage, and leakage monitoring at active carbon capture and storage sites.